2008
DOI: 10.1590/s1806-37132008001000004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de refluxo gastroesofágico em pacientes com doença pulmonar avançada candidatos a transplante pulmonar

Abstract: Objective: To assess the esophageal function profile and the prevalence of gastroesophageal reflux (GER) in lung transplant candidates. Methods: From July of 2005 to November of 2006, a prospective study was conducted involving 55 candidates for lung transplantation at the Santa Casa de Misericórdia Hospital in Porto Alegre, Brazil. Prior to transplantation, patients underwent outpatient stationary esophageal manometry and 24-h esophageal pH-metry using one and two electrodes. Results: Abnormal esophageal mano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
1
4
0
5
Order By: Relevance
“…Symptomatic and clinically silent reflux has been detected in bronchiectasis, with the prevalence from 26% to 75%, and aspiration of gastric contents in the respiratory tree is not rare in patients with GER [19,20]. In a group of patients with advanced lung disease including bronchiectasis manometry showed that 57% of patients had LES hypotonia and 14% had UES hypotonia [21]. Similar results were found in the seven patients of our study.…”
Section: Discussionsupporting
confidence: 85%
“…Symptomatic and clinically silent reflux has been detected in bronchiectasis, with the prevalence from 26% to 75%, and aspiration of gastric contents in the respiratory tree is not rare in patients with GER [19,20]. In a group of patients with advanced lung disease including bronchiectasis manometry showed that 57% of patients had LES hypotonia and 14% had UES hypotonia [21]. Similar results were found in the seven patients of our study.…”
Section: Discussionsupporting
confidence: 85%
“…A number of possible mechanisms originating from a gastrointestinal or respiratory perspective may increase the vulnerability to GERD in those with COPD. Although esophageal motility studies have not been extensively applied, reduced daytime and nocturnal esophageal peristalsis 40 , 56 , 81 and a decrease in UES 82 , 83 and LES pressure has been demonstrated in those with severe COPD. 11 , 40 , 64 , 82 Change in LES pressure may be partially attributed to smoking and the effects of nicotine.…”
Section: Possible Contributing Factors To Gerd In Copdmentioning
confidence: 99%
“…However, the relationship of reflux to clinical presentation or its association with lung disease severity was not evaluated [54]. Similar results were found in a study of seven patients with advanced bronchiectasis awaiting lung transplantation, with 33% experiencing an increased number of distal reflux episodes, specifically in the supine position [55]. In addition, manometry studies showed LOS hypotonia in 57% of those patients with upper oesophageal sphincter hypotonia in 14% of patients.…”
Section: Gor In Bronchiectasismentioning
confidence: 87%
“…In addition, manometry studies showed LOS hypotonia in 57% of those patients with upper oesophageal sphincter hypotonia in 14% of patients. This suggests that the gastrointestinal contributions to GOR which have been identified in patients with chronic obstructive pulmonary disease, cystic fibrosis, and interstitial lung disease [54, 55] may also be apparent in bronchiectasis. …”
Section: Gor In Bronchiectasismentioning
confidence: 99%